Aboriginal Well-being in Four Countries: An Application of the UNDP's Human Development Index to Aboriginal Peoples in Australia, Canada, New Zealand, and the United States - Cooke, M.; Mitrou, F.; Lawrence, David; Guimond, E.; Beavon, D. (Thompson Books, 2007)
An adaptation of the UNDP’s Human Development Index is used to compare the wellbeing of Aboriginal and non-Aboriginal populations in Australia, Canada, New Zealand, and the United States between 1991 and 2001. Using Census education and income measures, and official estimates of life expectancy, we find that despite improvements in the overall well-being of Aboriginal populations, disparities between Aboriginal and non-Aboriginal people widened in some cases. Aboriginal people in most of these countries fell behind in educational attainment, compared to non-Aboriginal populations. Incomes improved over the entire period, but fell in most of these countries between 1991 and 1996. Overall, Aboriginal populations in Australia and New Zealand had lower scores than in Canada and the U.S. However, whereas the Maori scores improved considerably between 1991 and 2001, those of the Australian Aboriginal population did not. American Indians and Alaska natives had the highest overall development scores, and smallest gaps between Aboriginal and non-Aboriginal people were found in the U.S.